Digital business platforms: the power of digital transformation on mobile devices (Research, Society and Development, 2020)
The purpose of this research is to study how smartphone users are adapting to digital transformation (TD). TD is the technology application for building new business models, processes, software and systems that result in more profitable revenue, greater competitive advantage and greater efficiency. The methodology chosen for this project consists of an exploratory study using bibliographic research methods and a survey of users using digital business platforms. The goal of this research has been achieved because we have been able to study how smartphone users are adapting to digital transformation using digital applications and platforms.